2001
DOI: 10.1034/j.1399-3038.2001.012004224.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation treatment: Errors in application and difficulties in acceptance of the devices are frequent in wheezy infants and young children

Abstract: The recent availability of small-volume spacers has facilitated the general use of inhaled treatment in infants. The purpose of this study was to evaluate any errors made by parents when using this new inhalation technique and the child's behavior during the inhalation. Ninety-four young children (61% boys) under 5 years of age were enrolled in the study. Inhalation treatment was recommended either by a general practitioner or by a pediatrician. Data concerning treatment regimens, the ability of parents to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
2
24
0
3
Order By: Relevance
“…Many research have shown that a high proportion of children do mistakes while using inhaled treatments (10,13,23). Lack of cooperation in young children especially hand mouth coordination may interfere with effective inhalation therapy with MDI (13,24,25). It has been demonstrated that the most common mistakes include not exhaling before starting, not shaking the MDI and inhaling for a very short time (10,13,21,(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many research have shown that a high proportion of children do mistakes while using inhaled treatments (10,13,23). Lack of cooperation in young children especially hand mouth coordination may interfere with effective inhalation therapy with MDI (13,24,25). It has been demonstrated that the most common mistakes include not exhaling before starting, not shaking the MDI and inhaling for a very short time (10,13,21,(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of cooperation in young children especially hand mouth coordination may interfere with effective inhalation therapy with MDI (13,24,25). It has been demonstrated that the most common mistakes include not exhaling before starting, not shaking the MDI and inhaling for a very short time (10,13,21,(23)(24)(25)(26)(27). Similar with other studies, common mistakes detected in our study were lack of mouth rinsing after use followed by lack of exhalation before inhaling the drug and not shaking the inhaler before use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations